Provision Of Avocado And Honey In Reducing Hypertension In Pregnant Women - Podungge, Yusni; Yanti , Febri Dwi; Slamet , Nangsih Sulastri; Toluli , Teti Sutriyati; Madania, Madania (Universitas Airlangga, 2023)
High blood pressure or hypertension in pregnant women can cause low birth weight baby. Based on the results of previous studies, provision of avocados can stabilize blood pressure become, gradually decrease and can be used as an alternative to non-pharmacological drugs. Local honey is also used because it has many health benefits and as a natural sweetener. The purpose of the study was to analyze the effect of avocados and local honey provision on hypertension in pregnancy at the Gorontalo City Health Center. This type of research is quantitative with pseudo-experimental methods with a one group pretest and posttest design approach. Avocados were given as much as 100 grams and local honey as much as 20 ml, avocado fruit is stirred together with local honey, then consumed after meals in the morning or evening. The sampling technique used is purposive sampling. Wilcoxon's test results showed 29 respondents experienced a systolic decrease and 10 respondents experienced a diastolic decrease after being given processed avocado and honey for seven days. It was found that there was an effect of giving processed avocados and honey on a significant decrease in systolic pressure with a p value < 0.005, but there was no effect of giving processed avocados and honey on reducing diastolic pressure p > 0.005 (0.767). In conclusion, processed avocados and honey can lower the blood pressure of pregnant women so it can be used as food alternatives consumed by pregnant women.